Proteomic characterization of clinical Candida glabrata isolates with varying degrees of virulence and resistance to fluconazole - Pamela El Khoury; Ahmad Zeidan; Roy A. Khalaf (PLoS ONE, 2025)
Candida glabrata, an opportunistic fungal pathogen, is a significant contributor to mortality among individuals with weakened immune systems. Antifungal drugs such as azoles work by inhibiting the Erg11 enzyme, altering the conversion of lanosterol to ergosterol. Resistance to azoles is increasing among Candida species worldwide, and in Lebanon. This study aims to determine the identity of cell wall proteins that could be involved in resistance and virulence in Candida glabrata Lebanese hospital isolates. Four isolates with varying degrees of resistance and virulence to fluconazole were subjected to proteomic analysis. Cell wall proteins of each isolate were extracted and analyzed using MALDI TOF TOF mass spectrometry to identify proteins responsible for virulence and resistance under exposure to fluconazole. Results showed the exclusive presence of efflux pumps such as Cdr1 and Pdr1 after exposure to fluconazole, in addition to other resistance mechanisms such as activation of multidrug transporter proteins and specific response pathways such as the RIM 101 pathway that could be involved in drug resistance and adhesion. Proteomic profiling exhibited proteins differentially detected in the virulent isolates such as the autophagy related proteins Atg 11 and Atg16, and stress response proteins Sgf11 and Alg2. In conclusion, our study suggests several mechanisms that contribute to resistance and virulence in C. glabrata.